2019
DOI: 10.3390/ani9100739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Threonine Levels on Intestinal Immunity and Antioxidant Capacity Based on Cecal Metabolites and Transcription Sequencing of Broiler

Abstract: This study aimed to determine the effects of different dietary threonine levels on the antioxidant and immune capacity and the immunity of broilers. A total of 432 one-day-old Arbor Acres (AA) broilers were randomly assigned to 4 groups, each with 6 replicates of 18 broilers. The amount of dietary threonine in the four treatments reached 85%, 100%, 125%, and 150% of the NRC (Nutrient Requirements of Poultry, 1994) recommendation for broilers (marked as THR85, THR100, THR125, and THR150). After 42 days of feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It has been reported that increasing levels of L-Thr improved the antioxidant capacity [ 33 , 59 ] by the best effects at 125% of the NRC; 1994 [ 32 ] recommended amounts. In the present study, the concentrations of SOD and CAT were not affected by the treatments, but a markable positive change in the GPX level was observed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that increasing levels of L-Thr improved the antioxidant capacity [ 33 , 59 ] by the best effects at 125% of the NRC; 1994 [ 32 ] recommended amounts. In the present study, the concentrations of SOD and CAT were not affected by the treatments, but a markable positive change in the GPX level was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of sardine samples, a high correlation (R 2 ≥ 0.94) was also obtained for free and total tryptophan content. Accordingly, all these amino acids have been previously reported to have antioxidant properties in several model systems [ 41 , 42 , 43 ]. For elastase and tyrosinase inhibition activities, the highest correlation coefficients (R 2 ≥ 0.8) were obtained for total protein content and free arginine, respectively, suggesting that these compounds could have an important role in the potential anti-ageing and anti-hyperpigmentation effect of fish industry waste streams extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Next, threonine synthase converts homoserine phosphate to threonine (Raïs et al 2001 ). Its antioxidant boosts the immune system’s ability to fight free radicals, protecting the body's equilibrium (Ji et al 2019 ; Egbujor et al 2020a ). Dietary threonine elevates mRNA levels of NRF2 and its dependent antioxidant enzymes and improves growth performance and muscle growth (Zhao et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%